Distributed and Parallel Processing of Location based spatial query with Approximate Transformation - Priya, M.; Kalpana, R. (2017 Ninth International Conference on Advanced Computing (ICoAC), 2017)
Location Based Services is the popular and geo sensitive service implicated over the smart phone by the internet. Nowadays these systems find its own enhancement, as they are using device's real time geographical information to provide information and entertainment. It allows the user to get the response to the query based on their current location there by location becomes the most basic context for the user. For example, these services are used to check for restaurants, coffee shops to get the business reward from the nearest shop or to track the location of a person. The user of the smart phone has certain limitations to overcome when they are using these services. The data size to be handled and the size of the memory are those main issues which influence the speed of query processing of these devices. In this paper, a new distributed index structure based on vantage point transformation technique is introduced to improve both the query space and the data space of the resulting query. The onus of this technique is to produce the better improvement in execution of the parallel analytical algorithm in query processing. This methodology not only improves the efficiency of the system but also reduces the number of false positives and false negatives.